Enhanced membrane binding of autoantibodies to cultured keratinocytes of systemic lupus erythematosus patients after ultraviolet B/ultraviolet A irradiation. - Golan, T D (1992)
Although sunlight is known to induce skin lesions in patients with systemic lupus erythematosus (SLE) and to exacerbate systemic manifestations, the underlying mechanisms remain obscure. We report experiments that show enhanced binding of IgG autoantibodies to the cell surface membrane of ultraviolet-B (UVB) irradiated (200-1,600 J/m2) cultured SLE keratinocytes in 10 out of 12 such cell strains. The autoantibody probes showing increased binding were directed against the soluble intracellular antigens, Sm, RNP, SSA/Ro, SSB/La, whereas serum with anti-dsDNA activity did not demonstrate such binding. Control keratinocytes from several sources shared low level binding of autoantibodies after ultraviolet light exposure. In addition, 4/6 UVB-sensitive SLE strains showed increased autoantibody binding to the surface of SLE keratinocytes after UVA exposure (50-150 kJ/m2), but of lower magnitude. When UVB-sensitive nonirradiated SLE strains were exposed to autologous serum, 3/8 sera demonstrated a striking increase in IgG binding, which increased further after UVB exposure. Enhanced expression of saline-soluble intracellular antigens on the cell surface membrane of patient, but not control, keratinocytes may, in part, explain the photosensitivity of patients with SLE.